2015
DOI: 10.1155/2015/413897
|View full text |Cite
|
Sign up to set email alerts
|

The Oncofetal Protein IMP3: A Novel Grading Tool and Predictor of Poor Clinical Outcome in Human Gliomas

Abstract: Morphologic criteria illustrated in WHO guidelines are the most significant prognostic factor in human gliomas, but novel biomarkers are needed to identify patients with a poorer outcome. The present study examined the expression of the oncofetal protein IMP3 in a series of 135 patients affected by high-grade (grade III and IV) gliomas, correlating the results with proliferative activity, molecular parameters, and clinical and follow-up data. Overall, IMP3 expression was higher in glioblastomas (68%) than in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In the present study, we found that high IMP3 expression was significantly correlated with high grade of glioma patients, and validated its high expression in glioma cells. Consistent with our data, Del Gobbo A et al suggested that IMP3 staining could identify a subgroup of patients with poor prognosis and at risk of recurrence in high-grade gliomas, indicating that IMP3 may act as a novel grading tool and predictor of poor clinical outcome in human gliomas 16…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that high IMP3 expression was significantly correlated with high grade of glioma patients, and validated its high expression in glioma cells. Consistent with our data, Del Gobbo A et al suggested that IMP3 staining could identify a subgroup of patients with poor prognosis and at risk of recurrence in high-grade gliomas, indicating that IMP3 may act as a novel grading tool and predictor of poor clinical outcome in human gliomas 16…”
Section: Discussionsupporting
confidence: 92%
“…A first series consisted of 54 patients that underwent surgery between 2013 and 2014, of which both fresh and archival neoplastic tissue could be retrieved for molecular or histological analyses respectively (Gene expression series). A second set of 187 patients that consecutively underwent surgery between 2008 and 2010 was enrolled for retrospective investigations on formalin-fixed paraffin-embedded tissues (Tissue microarray series) as previously described [ 40 ]. All patients were treated with surgical resection of the lesion and nobody received a merely diagnostic procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Following histological diagnosis, all patients affected by high grade gliomas (HGG; grades III and GBM) underwent concomitant chemo-radiation therapy according to the Stupp's protocol [ 42 ]. Follow-up data was available for GBM patients and it consisted of neuro-oncological assessment and brain MRI with gadolinium every 3 months as described [ 40 ]. Tumor progression was defined according to MacDonald's criteria [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor II mRNA-binding protein 3(IMP3) belongs to IMP family that consists of IMP1, IMP2, and IMP3. IMP family members have a significant role in RNA trafficking and stabilization, cell growth as well as cell migration during the early stages of embryogenesis (6). IMP3 is a protein encoded by gene IGF2BP3 which is located on chromosome 7p11.2 (7).…”
Section: Introductionmentioning
confidence: 99%